IDENTITY POLITICS IN THE 2019 INDONESIAN GENERAL ELECTIONS: ITS SIGNIFICANCE AND LIMITATION - Hanan, Djayadi (Universitas Padjadjaran, 2020)
Identity politics was significant in 2019 Indonesian general elections. The result of the election however, seems to show that identity was only significant in presidential but not in legislative election. Given that the legislative and presidential elections are conducted concurrently, it is logical to assume that what is significant in the presidential election will also be significant for the legislative election. This paper tries to briefly answer several questions. Is identity politics really rising? Why does it seem to be significant only in the presidential and not the legislative election? If identity politics in the presidential election is important, assuming that the incumbent is mostly the target of that politics, why did the incumbent still win? What are the implications of this for Indonesian democracy? Data of the study were taken from the Saiful Mujani Research and Consulting (SMRC) and the Indonesian Survey Institute (LSI) surveys and exit poll. Theoretical guidance for the discussion will be mainly based on the voting behavior and identity politics literature. The study indicates that identity politics was rising and significantly in play during this election, including by using fake news. However, the impact of identity politics is limited by the fundamental factors (such as public evaluation on the incumbent), making it fail to be a deciding factor in presidential election. Importantly, the multipolar nature of competition in legislative election made identity politics difficult to exert decisive effect.